Effect of radiotherapy for rectal cancer on female sexual function: a prospective cohort study. Issue 5 (3rd December 2019) - Svanström Röjvall, A.; Buchli, C.; Bottai, M.; Ahlberg, M.; Flöter‐Rådestad, A.; Martling, A.; Segelman, J.
Abstract : Background: Clinical experience and limited data show that female sexual function is influenced negatively by preoperative radiotherapy (RT) for rectal cancer. The aim of this prospective study was to investigate the impact of RT on sexual function and ovarian reserve measured by levels of anti‐Müllerian hormone (AMH). Methods: Women with stage I–III rectal cancer scheduled for surgery with or without preoperative (chemo)RT were included and followed for 2 years. Female Sexual Function Index (FSFI) questionnaire responses and blood samples for hormone analyses, including AMH in women aged 45 years or less, were collected at baseline and during follow‐up. Results: In the group of 109 women who received preoperative RT, median scores in all FSFI domains decreased over time, as did the total FSFI score (from 18·5 (range 2·0–36·0) at baseline to 10·8 (2·0–34·8) at 2 years; P  < 0·001). In the group of 30 women who did not receive preoperative RT, only satisfaction declined over time (from 3·2 (0·8–6·0) to 1·8 (0·8–6·0); P  = 0·012). In longitudinal regression analysis, the mean decline in FSFI total score was –9·33 (95 per cent c.i. –16·66 to –1·99; P  = 0·013) for women who had preoperative RT compared with those who did not, with adjustment for age, Psychological General Well‐being Index score and relationship with partner. A corresponding association was seen for arousal, lubrication, orgasm and pain. Five of six women aged 45 years or less with detectable serum levels of AMH at baseline had undetectable levels after RT. Conclusion: Preoperative RT was associated with impairment in sexual function in women with rectal cancer. This needs to be considered when discussing choice of treatment and rehabilitation. In younger women, undetectable AMH levels after RT indicate an irreversible loss of ovarian follicles. Abstract : Antecedentes: La experiencia clínica y los datos limitados que han sido publicados indican que la radioterapia (RT) preoperatoria por cáncer rectal influye negativamente en la función sexual femenina. El obejtivo de este estudio fue investigar prospectivamente el impacto de la RT en la funcion sexual y en la reserva ovárica evaluada por el nivel de hormona antimülleriana ( anti‐Müllerian hormone, AMH). Métodos: Las mujeres con cáncer rectal estadio I‐III en las que se planeaba un tratamiento quirúrgico con o sin (quimio)radioterapia ((chemo)radiotherapy (C)RT)) se incluyeron en el estudio y fueron seguidas durante 2 años. Se recogieron datos a nivel basal y durante el seguimiento del cuestionario del índice de función sexual femenina ( Female Sexual Function Index, FSFI), así como se obtuvieron muestras de sangre para los análisis hormonales, incluyendo AMH en mujeres de ≤ 45 años de edad. Resultados: En el grupo expuesto a RT ( n = 109), la mediana de las puntuaciones disminuyó a lo largo del tiempo en todos los dominios del FSFI y en la puntuación total del FSFI (de 18, 5 (2, 0‐36) a 10, 8 (2, 0‐34, 8), P < 0, 001). En el grupo no expuesto a RT ( n = 30), solamente el grado de satosfacciòn disminuyó a lo largo del tiempo (de 3, 2 (0, 8‐6, 0) a 1, 8 (0, 8‐6, 0), P = 0, 012). En el análisis longitudinal de regresión, la disminución media de la puntuación total del FSFI fue de ‐9, 33 (i.c. del 95% ‐16, 66; ‐1, 99), P = 0, 013) en el grupo expuesto a RT en comparacion con las mujeres no expuestas, durante los 2 años postoperatorios, ajustado por edad, índice de bienestar psicológico ( Psychological General Well Being Index, PGWI) y vida en pareja. Se observó una asociación correspondiente con la exitación, lubricación, orgasmo y dolor. Cinco de seis mujeres de ≤ 45 años de edad con niveles séricos detectables de AMH en situación basal presentaron niveles indetectables tras la RT. Conclusión: La RT preoperatoria se asociaba con alteración de la función sexual en mujeres con cáncer rectal. Este aspecto debe ser considerado a la hora de discutir la eleccion del tratamiento y la rehabilitación. En mujeres jóvenes, los niveles indetectables de AMH tras la RT indican una pérdida irreversible de folículos ováricos. Abstract : In this longitudinal cohort study of 139 women with rectal cancer, adding preoperative radiotherapy (RT) to surgery was associated with a decrease in several aspects of sexual function. In younger women, undetectable serum levels of anti‐Müllerian hormone after RT indicated irreversible loss of ovarian follicles. FSFI, Female Sexual Function Index. Impairs function